Prevalence of canine juvenile generalized Demodicosis in the Buenos Aires region, Argentina - Barrientos, Laura Soledad (2013)
Juvenile generalized demodicosis (JGD) is a common condition in dogs, and is associated with genetic and immunological factors. It is not a contagious or zoonotic disease, however, it is a serious disease, being potentially dangerous to affected animal´s lives. JGD affects most breeds of dog, though the predisposition of certain breeds has been noted. In this study, we analyzed 499 records of the Small Animal Hospital (Faculty of Veterinarian Sciences, National University of La Plata, Argentina) covering the period 1998–2006. In all cases, the dogs tested were primarily considered have had some type of dermatological disease, and among them 28 cases were eventually diagnosed as demodectic mange. Twenty-eight out of 499 cases found juvenile generalized demodicosis. Coincident with the data reported by other research, this study evidenced that certain breeds, such as Boxer, German Shepherd and mixed breed dogs had a higher prevalence of JGD. These results support the hypothesis that certain breeds of dogs have a greater predisposition to JGD.